Effect of long-term selenium supplementation on mortality: Results from a multiple-dose, randomised controlled trial - Rayman, Margaret P.; Winther, Kristian Hillert; Pastor-Barriuso, Roberto; Cold, Frederick; Thvilum, Marianne; Stranges, Saverio; Guallar, Eliseo; Cold, Søren (Free radical biology & medicine, 2018)
Selenium, an essential trace element, is incorporated into selenoproteins with a wide range of health effects. Selenoproteins may reach repletion at a plasma selenium concentration of ~ 125 µg/L, at which point the concentration of selenoprotein P reaches a plateau; whether sustained concentrations higher than this are beneficial, or indeed detrimental, is unknown. In a population of relatively low selenium status, we aimed to determine the effect on mortality of long-term selenium supplementation at different dose levels. The Denmark PRECISE study was a single-centre, randomised, double-blinded, placebo-controlled, multi-arm, parallel clinical trial with four groups. Participants were 491 male and female volunteers aged 60–74 years, recruited at Odense University Hospital, Denmark. The trial was initially designed as a 6-month pilot study, but supplemental funding allowed for extension of the study and mortality assessment. Participants were randomly assigned to treatment with 100, 200, or 300 µg selenium/d as selenium-enriched-yeast or placebo-yeast for 5 years from randomization in 1998–1999 and were followed up for mortality for a further 10 years (through March 31, 2015). During 6871 person-years of follow-up, 158 deaths occurred. In an intention-to-treat analysis, the hazard ratio (95% confidence interval) for all-cause mortality comparing 300 µg selenium/d to placebo was 1.62 (0.66, 3.96) after 5 years of treatment and 1.59 (1.02, 2.46) over the entire follow-up period. The 100 and 200 µg/d doses showed non-significant decreases in mortality during the intervention period that disappeared after treatment cessation. Although we lacked power for endpoints other than all-cause mortality, the effects on cancer and cardiovascular mortality appeared similar. A 300 µg/d dose of selenium taken for 5 years in a country with moderately-low selenium status increased all-cause mortality 10 years later. While our study was not initially designed to evaluate mortality and the sample size was limited, our findings indicate that total selenium intake over 300 µg/d and high-dose selenium supplements should be avoided. [Display omitted] •491 elderly Danes recruited to a randomised, controlled trial of Se supplementation.•A 300 µg dose of Se/d taken for 5 y increased all-cause mortality 10 y later.•Limitations: small sample size; mortality was not the primary trial endpoint.•Total Se intake over 300 µg/d from foods plus supplements should be avoided.